A valorização do profissional da educação e a carreira docente: a experiência do Governo de Frente Popular em Belém do Pará - LUZ, Sílvia Letícia D'Oliveira da (2008)
The Statute of the Education Profession which rules the career, and therefore the functional life of Education professionals, is the theme of this research intended to analyze policies on teacherscareer as well as their implications in the development of teacherswork, in the municipality of Belém (State of Pará, Brazil), from 1997 through 2004. This time period is relevant to the research for the city of Belém was under the administration of a self-nominated peoples government which will be called Popular Front government for the purposes of this study. The Popular Front government program brought forward the valorization of Education professionals, stressed the guarantees established in the Statute; at the same it time was pressured by those professionals demanding the government to enforce the Statute, specially teacherss rights therein stated. In order to analyze the policies issued by such government within the mentioned timeframe, we should understand, on the one side, the macro context within which the crisis of the capitalist system occurs and shapes reality; the insertion of Brazil in this reality and context; and the counter-reforms carried out in the Brazilian State designed, oriented to help overcome that crisis. On the other side, to understand the conceptual framework, and the role of a Popular Front government; the influence of the counter-reforms upon its policies; its political and economic stands concerning management. In this way, we expected to construe the effects upon teacherswork from the dynamics of those factors, in Belém. Therefore, specific research objectives were defined, namely: (1) to identify the consequences of the systemic crisis of capitalism, and those of the States role upon teacherslabor; (2) to analyze the counter-reforms of the Brazilian State from 1990 on, and its effects upon teacherswork; (3) to identify some characteristics of the Popular Front government, in Belém, as well as its program prospects regarding valorization of Education professionals; (4) to assess both the policies made by such government, and the outcomes of its implementation related to the teacherscareer in Belém. We departed from a historical analysis of the phenomenon under investigation based upon the theoretical support of selected authors, mostly Antunes (1995; 1999; 2004), Brzezinski (2007), Chesnais (1996), Engels (1977), Enguita (1991), Lênin (1986; 1986a), Marx (1980), Maués (2003; 2005; 2006), Moreno (2003; 2003a), Oliveira (2003), among others. Besides, we resorted to a number of legal and governmental documents, as well as to pertinent publications issued by two labor unions, namely the National Confederation of Workers in Education (CNTE) and the Union of Workers in Public Education of [the State of] Pará (SINTEPP), that helped to analyze the chosen categories career, remuneration, teachers education, and working conditions in the schools environment. Data and information were obtained also from empirical research, in order to sense, within a contradictory set of relations, the policies affecting teachers career, the popular front government, and the teachers organized movement. For this purpose some Education professionals were selected for semi-structured interviews, on the grounds of functional as well as political criterea; as for the functional ones, seven professionals were selected, one of them having a coordination position in the Municipal Department of Education; as for the political criteria two Education professionals participated in the research who held leadership positions in the SINTEPP. The literature review, and the methodological procedures mentioned above allowed for the conclusion that the enforcement of the Statute of the Education Profession, specally the teachers rights stated in it, and due, assured by law, would make it possible career development and valorization, mainly with respect to salary, education, and working conditions. The period of time examined was marked by effervescence in both labor and political terms as Education professionals chose to struggle for their rights boldly challenging a progressist government.